Antimicrobial activity of essential oils and natural plant extracts against Listeria monocytogenes in a dry‐cured ham‐based model. (23rd August 2021) - dos Santos, Luciana R; Alía, Alberto; Martin, Irene; Gottardo, Franciele M; Rodrigues, Laura B; Borges, Karen A; Furian, Thales Q; Córdoba, Juan J
Abstract: BACKGROUND: Listeria monocytogenes is a widespread common contaminant in food production facilities during preparation, storage, and distribution, and minimally processed ready‐to‐eat products are considered at high risk of contamination by this bacterium. Increased antibiotic resistance has led researchers to search for plant‐based natural alternatives to control pathogenic microorganisms. Among these products, essential oils and plant extracts have previously shown antimicrobial activity and are possible alternatives to manage food pathogens. In this study, commercial essential oils (cinnamon, clove, oregano, ginger, and thyme) and plant extracts (pomegranate, acorn, olive, strawberry tree, and dog rose) were tested against L. monocytogenes in a dry‐cured ham‐based model. RESULTS: Essential oils and plant extracts were screened by agar diffusion and minimum inhibitory concentration for anti‐ L. monocytogenes activity. Cinnamon, pomegranate, and strawberry trees returned the strongest results and were therefore evaluated in a dry‐cured ham‐based medium assay with water activity of 0.93 or 0.95. The 10% essential oil of cinnamon was capable of completely inhibiting bacterial growth, while strawberry tree and pomegranate extract also showed antilisterial activity ( P  > 0.05). Water activity influenced the bacterial count of L. monocytogenes in a dry‐cured ham‐based medium. CONCLUSIONS: There was a reduction in L. monocytogenes with the application of cinnamon essential oil but, because of the negative sensory impact of this particular compound in meat products, we suggest the use of pomegranate or strawberry tree for the biocontrol of Listeria in ready‐to‐eat products. © 2021 Society of Chemical Industry.